Oral Neurothekeoma of the Right Buccal Mucosa - Alex C. Tham; Nandini L. Chilagondanahalli; Manish M. Bundele; Jeevendra Kanagalingam (Case Reports in Otolaryngology)
Oral neurothekeoma or nerve sheath myxoma is a rare benign oral tumour of nerve sheath origin. Historically, this tumour has been subclassified as myxoid (classic), mixed, or the cellular type, depending on the amount of myxoid stroma and cellularity. We present a case of oral neurothekeoma (mixed type) of the buccal mucosa. The tumour was completely excised. No recurrence was detected in the last 3 years after local excision.